Residencia estudiantil - Sector 10 - escala barrial - Romo Recalde, Mishell Jeraldine (2019)
This work was based on the observation and assessment of the needs in terms of the design of a student residence center in the sector with the largest number of universities, this being La Mariscal. Through methodologies investigative, quantitative and qualitative objectives were determined, which allowed to develop a proposal that meets a relationship between the student residence and the environment, achieving that the residence has complementary areas which will seek the benefit of the external user. The Student Residence project is the result of the network of facilities proposed for the revitalization of the La Mariscal sector, this approach was made in the POU of Workshop ARO960 in the 2018-2 semester by students of the University of the Americas. In this way, this project was developed in four phases consisting of background, research, conceptualization and spatial proposal. In this way, the result was the implementation of urban and architectural parameters, as well as constructive, structural and environmental parameters, which will benefit a successful integration into the environment. La Mariscal sector, being a tributary of university students, is enriched by the proposal made, since it includes the accommodation service for 134 students between 18 and 34 years of age. Said residence will have all the housing conveniences and at the same time has a great attendance of communal areas of services and equipment such as workshops, multipurpose room, among others, which will allow the project to have one of the best offers of equipment in relation to other student residences.